Mediation analysis of the relationship between sex, cardiovascular risk factors and mortality from coronary heart disease: Findings from the population-based VHM&PP cohort. Issue 1 (November 2015) - Fritz, Josef; Edlinger, Michael; Kelleher, Cecily; Strohmaier, Susanne; Nagel, Gabriele; Concin, Hans; Ruttmann, Elfriede; Hochleitner, Margarethe; Ulmer, Hanno
Abstract: Background: In Europe, annually about 77, 000 women, but 253, 000 men die prematurely from coronary heart disease (CHD) before the age of 65 years. This gap narrows with increasing age and disappears after the eighth life decade. However, little is known regarding the contribution of cardiovascular risk factors to this sex difference. Objective: We investigated to what extent men's higher risk of dying from CHD is explained through a different risk factor profile, as compared to women. Methods: Mediation analysis technique was used to assess the specific contributions of blood pressure, cholesterol, glucose, and smoking to the difference between men and women regarding CHD mortality in a large Austrian cohort consisting of 117, 264 individuals younger than 50 years (as a proxy for pre-menopausal status) and 54, 998 older ones, with 3892 deaths due to CHD during a median follow-up of 14.6 years. Results: Adjusting for age and year of examination, we observed a male versus female CHD mortality hazard ratio (HR) of 4.7 (95% CI: 3.4–5.9) in individuals younger than 50 years, of which 40.9% (95% CI: 27.1%–54.7%) was explained through risk factor pathways, mainly through blood pressure. In older participants, there was a HR of 1.9 (95% CI: 1.8–2.0) of which 8.2% (95% CI: 4.6%–11.7%) was mediated through the risk factors. Conclusion: The extent to which major risk factors contribute to the sex difference regarding CHD mortality decreases with age. The female survival advantage was explained to a substantial part through the pathways of major risk factors only in younger individuals. Highlights: Premature mortality rate from CHD is still substantially lower in women. We estimated the contribution of major risk factors to this gender difference. BP and TC explain one third of the survival benefit in pre-menopausal women. In older persons, risk factors contribute much less to the mortality difference.